The Belt & Road Initiative and Its Impact on Central Asia Kazakhstan: A Case Study - Hanspal, Amandeep Singh (New Dynamics in Asia, 2020)
China’s Belt and Road Initiative is an ambitious plan which can be termed as part of a Chinese grand strategy that seeks to mitigate its internal weaknesses and project power outwards, underpinned by its economic surplus. Central Asia is at the heart of the land road component of this project. This paper briefly looks at China’s motives behind the project and then delves into the historical context and evolution of Central Asia. It further highlights the geographical logic behind Central Asia’s importance to the initiative and how it shapes the narrative. As a case study, Kazakhstan, due to its sheer size and proximity, is highlighted by looking at its significance to the Belt and Road Initiative and the visible impact, potential opportunities and pitfalls for the country.